Induction chemotherapy for locally advanced nasopharyngeal carcinoma treated with concurrent chemoradiation: A systematic review and meta-analysis. Issue 1 (October 2018) - Tan, Teng Hwee; Soon, Yu Yang; Cheo, Timothy; Ho, Francis; Wong, Lea Choung; Tey, Jeremy; Tham, Ivan W.K.
Abstract: Purpose: To determine if the addition of induction chemotherapy (IC) to concurrent chemoradiation (CCRT) in locally advanced nasopharyngeal carcinoma (LA-NPC) can improve survival. Methods: We performed a meta-analysis of both randomized controlled trials (RCTs) and observational studies (OBS) to compare the effects of addition of IC to CCRT versus (vs) CCRT alone on overall survival (OS), progression free survival (PFS), distant metastasis-free survival (DMFS) and adverse events (AE) in LA-NPC. We searched MEDLINE for eligible studies comparing IC plus CCRT vs CCRT for LA-NPC from Jan 1996 to May 2017. We selected RCTs and OBS that included patients with non-metastatic, LA-NPC who received IC followed by CCRT or CCRT alone. Three reviewers independently assessed the abstracts for eligibility. We assessed the methodological quality of the included studies using the MERGE criteria. We performed the meta-analysis with random effects model. We used the GRADE approach to appraise the quality of evidence from RCTs. The primary outcome was OS; secondary outcomes included PFS, DMFS and AE. Results: We found six RCTs and five OBS including 2802 patients with low to moderate risk of bias in their methodological quality. There was high quality evidence from the RCTs that IC improved PFS (HR 0.69, 95% CI 0.57–0.84, P  = 0.0003, I 2  = 0%) and OS (HR 0.77, 95% CI 0.60–0.98, P  = 0.03, I 2  = 0%) significantly and was associated with more frequent AE. The estimates of IC effects from RCTs and OBS were similar (PFS HR 0.69 vs 0.71, interaction P (IP) = 0.92; OS HR 0.77 vs 0.58, IP = 0.27). Conclusions: IC delays disease progression and improves survival significantly for LA-NPC treated with CCRT, and was associated with more toxicity. There were no divergent results between RCTs and OBS. IC followed by CCRT can be considered one of the standard treatment options for LA-NPC.